Eosinophilic myocarditis during treatment of acute myeloid leukaemia: cardiac magnetic resonance in the very early phase mimicking triple-vessel coronary artery disease: a case report. Issue 4 (17th April 2023) - Salihu, Adil; Stadelmann, Raphael; Solimando, Emilie; Schwitter, Juerg
Abstract: Background: Chemotherapy of acute myeloid leukaemia (AML) can cause a broad spectrum of cardiotoxic effects. Cardiac magnetic resonance (CMR) is key for the diagnosis of eosinophilic myocarditis (EM) defined by the presence of sub-endocardial necrosis and fibrosis. This case report describes the picture of severe triple-vessel ischaemia due to infiltration of eosinophilia without atherosclerotic coronary artery disease (CAD). Case summary: A 57-year-old woman was diagnosed with AML requiring chemotherapy. Three days after initiation of chemotherapy, the patient presented with chest pain and new left ventricular (LV) dysfunction and hyper-eosinophilia. A CMR examination initially was compatible with severe triple-vessel ischaemia. Tissue characterization by CMR was not done due to severe dyspnoea promoting the differential diagnosis of triple-vessel CAD or chemotherapy-induced triple-vessel coronary spasm. However, invasive coronary angiography excluded obstructive CAD. Severe LV dysfunction and troponin elevation persisted arguing against coronary vasospasm. Chemotherapy induced a massive increase in blood eosinophils, and EM was considered as most likely diagnosis. Immunosuppressive treatment improved the patient's status and a CMR later on confirmed the diagnosis of EM. Discussion: Chemotherapy-induced massive eosinophilia can cause widespread coronary micro-vascular infiltration mimicking severe triple-vessel CAD. Early CMR did not evaluate tissue composition, and EM was not considered which delayed adequate treatment. A complete CMR assessment is key to establish the correct diagnosis.